Measuring Local Revenue from The Tourism Sector in Bali Province - Dorkas Marline Lovrian Mautang; Ida Ayu Surasmi (Universitas Warmadewa, 2023)
This study aims to analyze the-effect-of-the-number-of-tourist-visits, length of stay of tourists and room occupancy rates on-local-revenue-from-the-tourism-sector-in-Bali Province. The-research method used is descriptive quantitative. The-data-used-in-this study-secondary-data-from-the-Bali Province Tourism Office. The technique used-is-multiple-linear regression. With-the-number-of-samples used, namely 30 months, from October 2019 to March 2022. The results showed that partially the-number-of tourist visits had a-positive-and significant-effect-on local revenue from the-tourism-sector-in-Bali Province, the-length-of-stay of tourists and the room occupancy rate had a negative and insignificant effect-on-local revenue from-the-tourism-sector-in-Bali Province. Simultaneously the number of tourist visits, length of stay of tourists and room occupancy rates have a significant influence-on-local-revenue from the tourism sector in Bali Province.